Aei 2015 2015
DOI: 10.1061/9780784479070.011
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Double Skin Façade (DSF) with High Performance Green Hybrid Fiber-Reinforced Concrete (HP-G-HyFRC) for Resilient and Sustainable Buildings

Abstract: Buildings are an integral part of the broader civil infrastructure that ensures our welfare, livelihood, safety, and security. However, the sector also represents a burden to the society. Globally, building sector accounts for about 40% of total primary energy use. Natural disasters such as windstorms or earthquakes can cost billions of dollars in damages to structural and non-structural components of buildings. In this study, a resilient and sustainable building envelope is proposed through an innovative air-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…[38,41,44,[67][68][69][70][71][72]74,77,78,81] and Material Effectiveness [40,47,63,66,[73][74][75][76]) from the selected records resulted from the literature review and selected records (keywords found in the records belonging to each thematic category in yellow stickers, research articles in light blue ones, review articles in blue ones, and conference papers in black ones). [38,41,44,[67][68][69][70][71][72]74,77,78,81] and Material Effectiveness [40,47,63,66,[73][74][75][76]) from the selected records resulted from the literature review and selected records (keywords found in the records belonging to each thematic category in yellow stickers, research articles in light blue ones, review articles in blue ones, and conference papers in black ones). [41,48,75,…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[38,41,44,[67][68][69][70][71][72]74,77,78,81] and Material Effectiveness [40,47,63,66,[73][74][75][76]) from the selected records resulted from the literature review and selected records (keywords found in the records belonging to each thematic category in yellow stickers, research articles in light blue ones, review articles in blue ones, and conference papers in black ones). [38,41,44,[67][68][69][70][71][72]74,77,78,81] and Material Effectiveness [40,47,63,66,[73][74][75][76]) from the selected records resulted from the literature review and selected records (keywords found in the records belonging to each thematic category in yellow stickers, research articles in light blue ones, review articles in blue ones, and conference papers in black ones). [41,48,75,…”
Section: Discussionmentioning
confidence: 99%
“…Figure A2. Clusters (specifically Indoor Comfort[38,41,44,[67][68][69][70][71][72]74,77,78,81] and Material Effectiveness[40,47,63,66,[73][74][75][76]) from the selected records resulted from the literature review and selected records (keywords found in the records belonging to each thematic category in yellow stickers, research articles in light blue ones, review articles in blue ones, and conference papers in black ones).…”
mentioning
confidence: 99%
“…Building motion from a discomfort as well as a structural and mechanical performance level/perspective has been studied to determine if DSFs can aid in these issues for tall buildings [15,106,107]. Other multi-disciplinary studies have looked at the materiality of DSFs in relation to sustainability [107,108]. These are important areas of research as designers are required to study more than just energy; for example, embodied carbon is another design factor.…”
Section: Dsf Research Threadsmentioning
confidence: 99%
“…Alongside modeling for structural performance, a holistic approach is needed to evaluate embodied energy, operational energy, and recurring embodied energy resulting from maintenance [8] and for sustainability [108]. Designers may consider Life Cycle Analysis and embodied carbon as a way to appraise design performance [183].…”
Section: Lca Modeling For Dsf Designsmentioning
confidence: 99%